2013
DOI: 10.1051/0004-6361/201218824
|View full text |Cite
|
Sign up to set email alerts
|

Warm gas in protostellar outflows

Abstract: Context. Observations of CO rotational transitions in the 0.3−0.4 millimeter range, now possible from exceptional sites on the ground, provide the opportunity of studying the warm component of molecular outflows in star-forming regions. Aims. This study aims to characterize the role of the warm gas in high-velocity and collimated outflows from Class 0 low-mass protostars. Methods. We used the CHAMP + heterodyne array on the APEX telescope to map the CO (6-5) and CO (7-6) emission in the wellknown Class 0 outfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…Finally, the outflow force in L1448 has been measured by different authors adopting different data and methods. In particular, the value originally measured with single-dish, low-J lineobservations (Bachiller et al 1990)has been confirmed with the analysis of high-resolution interferometric (Hirano et al 2010) and high-J CO (Gomez-Ruiz et al 2013;Y÷ld÷z et al 2014) observations. It is therefore unlikely that all those determinations are overestimated by a factor of 10.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, the outflow force in L1448 has been measured by different authors adopting different data and methods. In particular, the value originally measured with single-dish, low-J lineobservations (Bachiller et al 1990)has been confirmed with the analysis of high-resolution interferometric (Hirano et al 2010) and high-J CO (Gomez-Ruiz et al 2013;Y÷ld÷z et al 2014) observations. It is therefore unlikely that all those determinations are overestimated by a factor of 10.…”
Section: Discussionsupporting
confidence: 53%
“…High angular resolution observations in SiO lines (Dutrey et al 1997) were found in agreement with a structure of incomplete and fragmented bow-shocks caused by discrete episodes of ejection from the central star (’molecular bullets’). Strong H 2 O and high-J CO line emission was detected toward this and other L1448 bright spots by Nisini et al (2000, 2013), Santangelo et al (2012) and Gomez-Ruiz et al (2013) indicating the presence of very dense (∼ 10 6 cm −3 ) molecular gas at temperatures in excess of 500 K.…”
Section: The Source Samplesupporting
confidence: 59%
“…A multiline analysis of CS and its isotopic variations allowed to study the density structure of the molecular outflow (Gómez-Ruiz et al 2015). The line profiles can be well fitted by a combination of two exponential laws that are remarkably similar to what previously found using CO by Lefloch et al (2012).…”
Section: Chemical Evolution Along Star Formationmentioning
confidence: 99%
“…Mid-J CO transitions are good tracers of warm gas in molecular outflows compared to low-J transitions (Gomez-Ruiz et al 2013). Since we have found that CO (2-1) and CO (6-5)/(7-6) probe different gas (Section 3.3) and the step 3 summation maps likely trace the collimated jet better (Section 4.1.1), we use the CO (6-5) and (7-6) maps and their step 3 summation maps to study the shocked gas.…”
Section: Warm Gas Propertiesmentioning
confidence: 99%